High Spatiotemporal Near‐Infrared II Fluorescence Lifetime Imaging for Quantitative Detection of Clinical Tumor Margins - Zhen Chen; Linjian Huang; Duyang Gao; Zhouzhou Bao; Dehong Hu; Wei Zheng; Jing Chen; Jiuling Liao; Hairong Zheng; Zonghai Sheng (Advanced Science)
Abstract Accurate detection of tumor margins is essential for successful cancer surgery. While indocyanine green (ICG)‐based near‐infrared (NIR) fluorescence (FL) surgical navigation enhances the visual identification of tumor margins, its accuracy remains subjective, underscoring the need for quantitative approaches. In this study, a high spatiotemporal fluorescence lifetime (FLT) imaging technology is developed in the second near‐infrared window (NIR‐II, 1000–1700 nm) for quantitative tumor margin detection, utilizing folate receptor‐targeted ICG nanoprobes (FPH‐ICG). FPH‐ICG exhibits a significantly prolonged NIR‐II FLT (750 ± 7 ps vs 260 ± 3 ps) and increased NIR‐II FL brightness (FPH‐ICG/ICG = 3.8). In vitro and in vivo studies confirm that FPH‐ICG specifically targets folate receptor‐α (FRα) on SK‐OV‐3 ovarian cancer cells, achieving high‐contrast NIR‐II FL imaging with a signal‐to‐background ratio of 10.8. Notably, NIR‐II FLT imaging demonstrates superior accuracy (90%) and consistency in defining tumor margins compared to NIR‐II FL imaging (58%) in both SK‐OV‐3 tumor‐bearing mice and clinical tumor samples. These findings underscore the potential of NIR‐II FLT imaging as a quantitative tool for guiding surgical tumor margin detection.